Introducing an Organ Donor Registry is Saskatchewan - Amy Zarzeczny; Luiza Radu (McMaster University Library Press, 2021)
On 3 September 2020, Saskatchewan launched an organ donor registry that allows participants 16 years and older to register their intent to be an organ donor either online or using a paper form. Saskatchewan has historically performed poorly at a national level with low rates of organ donations. Saskatchewan's new registry is intended to increase the numbers of organ donors in the province, while also helping to modernize its organ donation system and ease donation conversations with families. Saskatchewan's introduction of this registry brought the province in line with other provinces and territories across Canada that use similar systems, and provided a response to the surge in public interest around organ donation that followed the Humboldt Bronco bus crash tragedy and related ``Logan Boulet Effect.'' The 2019-2020 and 2020-2021 provincial budgets included dedicated funding for the development and launch of the registry, which was accompanied by a media campaign to increase public awareness. Though it is too early to evaluate the success of the registry, early indications suggest donation rates will be a key evaluation metric. Registries are commonly thought to help increase public awareness of, and support for, organ donation, but improving Saskatchewan's organ donation rates will likely also require companion measures to strengthen the culture and practice of donation in the province.